Visual Pleasure in Kawabata Yasunari's Novella House of the Sleeping Beauties - Ida Purnama Sari; Wening Udasmoro (Bina Nusantara University, 2020)
The research discussed visual pleasure in Kawabata Yasunari’s novella “House of the Sleeping Beauties”. Women, whensubject to the male gaze, had often been the objects of sexual and visual pleasure. The novella described the nyotaimoripractice, in which sushi was served on the nude body of a woman for the object of male visual and sexual pleasure. Theresearch sought to dissect and explore visual pleasure in literary work and its central positioning. Using Laura Mulvey’stheory of male gaze and visual pleasure, and feminist literary studies, it employed content analysis as a method to uncover the phrases and paragraphs depicting visual pleasure in the novella. Firstly, the research finds that in practicing visual enjoyment, men use women as the objects of pleasure and fantasy. Secondly, men position women, their female bodies, and sexuality as markers of castration.